WHOLE-BODY VIBRATION TRAINING PROTOCOLS IN OBESE INDIVIDUALS: A SYSTEMATIC REVIEW - Melo,Fábio Antônio Tenório de (2019)
ABSTRACT Obesity is a chronic degenerative disease. Whole-body vibration (WBV) devices make it possible to control the intensity of exercises through their variables: frequency, amplitude and vibration time, thus enabling interventions in these populations. The objective of this study was to review the applications, protocols and results of WBV devices in obese individuals. A systematic literature review was conducted using the descriptors and terms verified in DeCS (LILACS and SCIELO) and MeSH (PubMED). Of the thirteen studies selected, seven used an experimental and six a quasi-experimental methodological design. Eleven studies analyzed chronic responses and two studies acute responses to WBV training. Frequency values ranged between 30 and 35 Hz, amplitude was around 2 mm, and in terms of intensity, most of the training protocols used a gradual increase in WBV throughout the intervention. Eight studies added dynamic exercises and extra loads to the WBV. The mean total WBV exposure time varied around 20’ distributed in 1 or 2 series, with vibration times of 30” to 60” and the same rest time. The mean frequency of interventions was around 2 to 3 times a week, with a mean intervention time of 10 months. The main results include: decrease in body weight and improvement in the physiological variables of oxygen absorption, bone mineral density and arterial profile, indicating that WBV can be a safe tool in the fight against obesity and its implications. Level of Evidence II. Systematic Review of Level II Studies.